TRADISI BAKAR TONGKANG: DARI BUDAYA KOMUNITAS MENJADI TONTONAN PUBLIK 2006-2019 - Hasanah, Dewi Nur; Erniwati, Erniwati (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
This research discusses the Barge Burning tradition of the Chinese community in Bagansiapiapi, which was originally only a community culture carried out by the Chinese community, until it finally changed to become a public spectacle celebrated by the entire community in 2006-2019. The aim of this research is to see why the ethnic Chinese barge burning tradition has changed from a community culture to a public spectacle and what forms of change in the barge burning tradition, which was originally a community culture, has become a public spectacle in 2006-2019. This research uses historical research methods. The results of the research show that the Bagansiapiapi Chinese ethnic barge burning tradition has undergone changes since 2006, because the Regional Government made it a regional cultural tourism event in Rokan Hilir Regency. There are values that have changed due to commercialization, namely the time of barge burning, previously ships were burned at night, since it became a tourist event the barge burning was carried out earlier, namely in the afternoon or evening. Then the shape and material of the ships changed, in the 18th century ships were made of bamboo and paper, since 2006 the materials used have been wood, bamboo and colorful paper. As a result of turning Bakar Tongkang into a tourist event, tourists are interested in seeing the celebration and coming to Bagansiapiapi and increasing the Regional Revenue Budget, as evidenced by the number of tourists which continues to increase every year.